T-cell receptor signaling in Schimke immuno-osseous dysplasia is SMARCAL1-independent - Marin, Ana V.; Jiménez-Reinoso, Anaïs; Mazariegos, Marina S.; Román-Ortiz, Elena; Regueiro, José R. (Frontiers in Immunology, 2022)
Schimke immuno-osseous dysplasia (SIOD) caused by mutations in SMARCAL1 is an ultra-rare disease characterized by specific facial features, skeletal dysplasia, and steroid-resistant nephrotic syndrome, which often leads to kidney failure and requires transplantation. Cellular (T-cell) deficiency, lymphopenia and infections have been frequently reported, but whether they are due to T cell-intrinsic defects in T cell receptor (TCR) signaling associated with SMARCAL1 deficiency or to T cell-extrinsic effects such as the impaired proliferation of hematopoietic precursors or T-cell-specific immunosuppression after renal transplantation remains unknown. We have explored the effects of SMARCAL1 deficiency on T-cell receptor signaling in primary vs immortalized T-cells from a 9-year-old SIOD patient under immunosuppression treatment, when compared to healthy donors. Immortalized T cells recapitulated the patient’s SMARCAL1 deficiency, as judged by their impaired response to gamma irradiation. The results indicated that TCR-mediated signaling was normal in SIOD-derived immortalized T cells but strongly impaired in the patient’s primary T cells, although rescued with TCR-independent stimuli such as PMA+ionomycin, suggesting that SIOD-associated T-cell signaling is not intrinsically defective, but rather the result of the impaired proliferation of hematopoietic precursors or of T-cell-specific immunosuppression. The lack of early thymic emigrants in our patient may support the former hypothesis.